8- Statutory Law, Patriarchy and Inheritance: Home ownership among Widows in Uganda - Asiimwe, Florence Akiiki (African Sociological Review, 2009)
This paper discusses the ways in which urban widows in Uganda are deprived of home ownership upon the death of their husbands. It is based on a qualitative research conducted in the middle-income areas of Kampala between 2004 and 2007. The results show that the institutional legal framework and the patriarchal customary practices and beliefs deprive widows of home ownership notwithstanding the gender sensitive Constitution. The study also shows that the special ways in which widows are able to inherit the matrimonial home upon the death of their husbands demonstrate the difficulty widows face to become home owners.